Prophetic Entrepreneurship To Improve Entrepreneurial Mental Readiness - Shanty Komalasari; Sri Anafarhanah (Journal of Educational, Health and Community Psychology, 2022)
Entrepreneurial mental readiness is an important thing that students need to have before starting a business. The results of the initial assessment show that students have low entrepreneurial mental readiness. Given the importance of mental readiness in entrepreneurship, the researchers arranged training in prophetic entrepreneurship to improve the students' mental readiness for entrepreneurship at UIN Antasari Banjarmasin. There were 82 research subjects, then divided into experimental and control groups each consisting of 41 people. The design used in this study was an untreated control group design with pre-test and post-test. Data analysis was carried out using Paired Sample T-Test to determine the effect of training prophetic entrepreneurship on the experimental and control groups before and after the training. The results of the analysis show that training prophetic entrepreneurship can improve student entrepreneurship mental readiness with an effectiveness of 57%.Keywords: Prophetic Entrepreneurship, Mental Readiness, Entrepreneurship